Financial Literacy for Increasing Sustainable Access to Finance in Nepal - Chaulagain, Ramesh Prasad (NRB Economic Review, 2015)
Recent policies and practices of Nepali financial sector are focused to establish financial institutions to increase people’s ‘access to finance’. As a result, the numbers of financial institutions licensed both by Nepal Rastra Bank and Government of Nepal are growing rapidly. All the institutions are doing the similar functions in the same market. The financial institutions licensed by Nepal Rastra Bank are classified into commercial banks, development banks, finance companies and micro finance development banks, whereas the Government of Nepal licenses to the saving and credit cooperative socieites (SACCOS). Despite the supply sided endeavors, the demand side considerations in financial sector is more silent. This creates a concern about the capability of people in consuming financial services. As a result, quality and sustainable access to finance are in question. Furthermore, the expansions of such institutions are also concentrated in urban, semi-urban and priviledged areas causing unequal distribution of institutions and limited access to finance. This situation has given rise to unhealthy competition among the actors focusing on earning rather than empowering the financial consumers. This paper explores how far the expansion of Banks and Financial Institutions including cooperatives assures the access to finance and its sustainability. The secondary data shows a significant growth of financial sector and an increment of number of people involved in financial transactions in the banking industry. However, the primary data of the study shows that such expansion is necessary but not sufficient condition to assure a sustainable access to finance. The study also explores the worth of financial literacy among the people both in urban and rural areas as one of the means to enhance people’s access to finance and its sustainability. The paper is based more on the discussion and analytical approach with a mix of secondary and primary sources of data.